Ceftriaxone and MC-100093 mitigate fentanyl-induced cardiac injury in mice: Preclinical investigation of its underlying molecular mechanisms - Abdullah F. AlAsmari; Mohammed M. Alshehri; Nemat Ali; Fawaz AlAsmari; Youssef Sari; Wayne E. Childers; Magid Abou-Gharbia; Metab Alharbi; Doaa M. Elnagar; Wejdan S. AL-Qahtani (Elsevier, 2024)
Drug addiction is considered a worldwide concern and one of the most prevailing causes of death globally. Opioids are highly addictive drugs, and one of the most common opioids that is frequently used clinically is fentanyl. The potential harmful effects of chronic exposure to opioids on the heart are still to be elucidated. Although β-lactam antibiotics are well recognized for their ability to fight bacteria, its protective effect in the brain and liver has been reported. In this study, we hypothesize that β-lactam antibiotic, ceftriaxone, and the novel synthetic non-antibiotic β-lactam, MC-100093, are cardioprotective against fentanyl induced-cardiac injury by upregulating xCT expression. Mice were exposed to repeated low dose (0.05 mg/kg, i.p.) of fentanyl for one week and then challenged on day 9 with higher dose of fentanyl (1 mg/kg, i.p.). This study investigated cardiac histopathology and target genes and proteins in serum and cardiac tissues in mice exposed to fentanyl overdose and β-lactams. We revealed that fentanyl treatment induced cardiac damage as evidenced by elevated cardiac enzymes (troponin I). Furthermore, fentanyl treatment caused large aggregations of inflammatory cells and elevation in the areas and volumes of myocardial fibers, indicating hypertrophy and severe cardiac damage. Ceftriaxone and MC-100093 treatment, However, induced cardioprotective effects as evidenced by marked reduction in cardiac enzymes (troponin I) and changes in histopathology. Furthermore, ceftriaxone and MC-100093 treatment decreased the levels of hypertrophic genes (α-MHC & β-MHC), apoptotic (caspase-3), and inflammatory markers (IL-6 & NF-κB). This study reports for the first time the cardioprotective effect of β-lactams against fentanyl-induced cardiac injury. Further studies are greatly encouraged to completely identify the cardioprotective properties of ceftriaxone and MC-100093.